Lingvocultureanalysisof proper namesinLaoshiworks (Journal of Oriental Studies, 2016)
This article analyzes the Lingvo culture as pecificsethno-linguistic, symbolic features of onomasticunit of Lao Shyprose. And also describes the relationship Lingvo culturein formation content onomasticon Chinese writer works with the national mentality, peculiarities of attitude, spiritual and moral values of the Chinese people.
Keywords: onomasticunits; names; concept; ethno-culturalin formation; lingvo culture.